Analysis and Design of Restaurant Information System using Unified Modeling Language - Agustinus Fritz Wijaya; Maylani Indah Rakhmawati (Soegijapranata Catholic University, 2019)
This research was done with the aim of facilitating the Admin access to process raw material inventory data which outlets and warehouses are located in different cities. The method used is the SDLC method, which is a method that uses several stages in system development ranging from System Planning, System Analyst, System Design, System Implementation, System Implementation, and System Maintenance. The result of this research is a system that can be accessed by admins to facilitate the work process.